DESIGNING A CURRICULUM IN PHYSICAL EDUCATION LEARNING - Bagus Cahyono Putro; Avi Kusuma Fatkhur; Alfredo Adam Gustavian; M. Ilham Akbar Santosa; M. A. Ma’ruf Alkatsiri; Bagus Cahyono Putro; Avi Kusuma Fatkhur; Alfredo Adam Gustavian; M. Ilham Akbar Santosa (Universitas Negeri Malang, 2024)
This writing aims to explain curriculum design, especially physical education, which bases the design on several important things. Designing a curriculum needs to pay attention to physical education schemes, competencies, learning approaches, standards, comparisons with the application of foreign curricula. The method used in this writing is conceptual descriptive writing. The writing stages include: 1) Determining the theme and topic, 2) Compiling the literature review, 3) Ensuring novelty, 4) Mapping the concept, 5) Developing a statement, 6) Checking the problem formulation, 6) Developing the concept, 7) Compiling the narrative, 8) Fixed framework. So, it can be concluded that the physical education curriculum is at least developed in a balanced way, meaning that the content in physical education is not only emphasized on mastering motor skills, but other values need to be developed.